Technology for the production of the substance of the drug donaxin hydrochloride (Texas Journal of Multidisciplinary Studies, 2022)
A technology has been created for the production of the substance donaxin hydrochloride from the aerial part of the donax plant. On the basis of the created technology, apparatuses were selected and a production line was installed. This line produced the first industrial samples of donaxin hydrochloride substances from the aerial part of donax.